Interleukin-12p35 knockout promotes macrophage differentiation, aggravates vascular dysfunction, and elevates blood pressure in angiotensin II-infused mice - Ye, Jing; Que, Bin; Huang, Ying; Lin, Yingzhong; Chen, Jiangbin; Liu, Ling; Shi, Ying; Wang, Yuan; Wang, Menglong; Zeng, Tao; Wang, Zhen; Hu, Haiying; et al. (Cardiovascular research, 2019)
Abstract Aims Numerous studies have demonstrated that inflammation is involved in the progression of hypertension. Inflammatory cytokines interleukin (IL)-12 and IL-35 belong to the IL-12 cytokine family and share the same IL-12p35 subunit. Accumulating evidence has demonstrated that IL-12p35 knockout (IL-12p35 KO) leads to cardiovascular disease by regulating the inflammatory response. This study aimed to investigate whether IL-12p35 KO elevates blood pressure in a hypertension mouse model. Methods and results Mice with angiotensin (Ang) II infusion showed marked aortic IL-12p35 expression; thus, aortic macrophages may be the main source of IL-12p35. Wild-type and IL-12p35 KO mice were infused with Ang II or saline. IL-12p35 KO promoted M1 macrophage differentiation, amplified the inflammatory response, aggravated vascular dysfunction, and elevated blood pressure in Ang II-treated mice. Then, some Ang II-infused mice were given phosphate buffer saline, mouse recombinant IL-12 (rIL-12), or rIL-35, and the results showed that rIL-12 but not rIL-35 treatment had an antihypertensive effect on Ang II-infused mice. In addition, detection of human plasma IL-12 levels in hypertensive patients and control subjects showed that IL-12 was significantly increased in hypertensive patients when compared with control subjects. In hypertensive patients, IL-12 levels were positively correlated with blood pressure. Conclusion IL-12p35 KO amplifies the inflammatory response and promotes blood pressure elevation in Ang II-treated mice. In addition, IL-12, but not IL-35, plays a protective role in the Ang II-induced hypertension model. Thus, IL-12 may be a novel therapeutic agent for the prevention and treatment of clinical hypertension.